IMPLEMENTASI PEMBELAJARAN AKIDAH AKHLAK DALAM MEMBENTUK KARAKTER SISWA KELAS VIII DI MTS NEGERI 2 SUKOHARJO - Hayati, Nadia Fadila; Hidayat, M. Yunan; Abdullah, Mu’in (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
Learning moral aqidah is one of the curricula taught at secondary education level which has a big influence on students' behavior, both in school life and outside of school. This research aims to find out how moral learning is implemented in shaping the character of Class VIII students at MTs Negeri 2 Sukoharjo. The approach in this research is a qualitative approach, using descriptive case study research. This research was conducted at MTs Negeri 2 Sukoharjo using data collection techniques in the form of observation and interviews. Aqidah Akhlak learning is used as a media for the process of forming polite character in students. This is supported by the role of Aqidah Akhlak teachers in directing and cultivating good moral character so that in the future students become good individuals in society. The culture of shaking hands before entering class at MTs Negeri 2 Sukoharjo is an inspiration for the polite character of students who need to be emulated in the millennial era.